2023
DOI: 10.3390/w15101817
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Water Environment Capacity Assessment Based on Control Unit Coupled with SWAT Model and Differential Evolution Algorithm

Abstract: Water pollution is a serious problem in China and abroad. Revealing the source types and their spatio-temporal characteristics is the premise of effective watershed management and pollution prevention. Since the national control unit can better match the administrative division, it was useful for the manager to control water pollution. Taking the Fenhe River Basin as the research area, a SWAT model based on the national control unit was established in this study to reveal the current situation of water quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The water pollution load carrying capacity was introduced as a pollution control goal for regional pollution control work [32,33]. By comparing the current load emission with the calculated load carrying capacity, it is possible to ascertain the exact rate of emissions that need to be reduced for the satisfaction of water quality reaching the target standards requirements.…”
Section: Load Allocation Based On Water Pollution Load Carrying Capac...mentioning
confidence: 99%
“…The water pollution load carrying capacity was introduced as a pollution control goal for regional pollution control work [32,33]. By comparing the current load emission with the calculated load carrying capacity, it is possible to ascertain the exact rate of emissions that need to be reduced for the satisfaction of water quality reaching the target standards requirements.…”
Section: Load Allocation Based On Water Pollution Load Carrying Capac...mentioning
confidence: 99%
“…Changes in land use can modify the hydrological processes, energy flow, and nutrient cycling, which consequently affect the surface water quality and ecological functions [19]. There are obvious differences in water quality in different spatial conditions [20]. Previous studies have shown that forestland had a primary interception effect on non-point source pollution, while farmland drainage is the key factor causing surface water eutrophication [21].…”
Section: Introductionmentioning
confidence: 99%